Penerapan Sanksi Atas Pelanggaran Hukum Disiplin Militer Dalam Sistem Peradilan Militer - Salmanita Shalsabella Pramudita; Irwan Triadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This court is regulated in Law Number 31 of 1997 concerning military justice, so that if a soldier commits a violation of the law, he will be subject to the court. As the author, I took the title: "The Urgency of Implementing Professional Ethics in Law Enforcement Efforts in Indonesia". We have great hope as writers that by writing this, we can provide benefits and knowledge to readers in accordance with its objectives. This research uses a normative juridical approach, namely by inventorying, studying and analyzing and understanding law as a set of regulations or positive norms in the legislative system that regulates human life. Based on the research results, it is known that the role of the Military Interest Principle in imposing disciplinary laws is highly prioritized in TNI institutions. It is hoped that in the future the TNI will be more professional and remain solid as a means of national defense but will still be guided by the law.